Preparation and characterization of RDX/BAMO-THF energetic nanocomposites. Issue 4 (2nd October 2018) - Chen, Teng; Li, Wanhui; Jiang, Wei; Hao, GaZi; Xiao, Lei; Ke, Xiang; Liu, Jie; Gao, Han
ABSTRACT: Novel 1, 3, 5-trinitro-1, 3, 5-triazine/3, 3-bis (azidomethyl) oxetane-tetrahydrofuran copolymer (RDX/BAMO-THF) energetic nanocomposites were successfully prepared by a facile sol–gel freezing–drying method. The as-prepared RDX/BAMO-THF energetic nanocomposites were characterized by Raman and Fourier transform infrared spectroscopy, which revealed that RDX particles were incorporated into BAMO-THF gel matrix. Scanning electron microscopy was used to characterize the morphology and the particle size of the as-obtained samples. The results showed that RDX particles were trapped in the BAMO-THF gel matrix and the particle sizes were in nanoscale. Differential thermal analyzer (DTA) was performed to determine the thermal decomposition behaviors of BAMO-THF, raw RDX and RDX/BAMO-THF nanocomposites. The results indicated that the thermal decomposition process of RDX/BAMO-THF nanocomposites was enhanced compared with that of BAMO-THF and RDX. The kinetic, thermodynamic and thermal stability parameters were calculated according to DTA analysis. The calculated results revealed that RDX/BAMO-THF nanocomposites presented high thermal reactivity. The results of impact sensitivities for RDX/BAMO-THF nanocomposites indicated the sensitivity was effectively reduced compared to raw RDX.